Reparation Labor–A Preliminary Analysis - Fisher, Paul (Quarterly Journal of Economics, 1946)
I. Opposition to compulsory labor after World War I, 313. — Emergence of more favorable views, 314. — Comparison with prisoners of war, 316. — Relation to other policies, 318. — II. Absorption of foreign forced labor, 321. — Labor mobility, 322. — Industrial techniques and state of the arts, 324. — III. Effects of foreign forced labor upon the country using it: the free market economy, 326; the directed economy, 329. — The problem of foreign trade, 334. — IV. Problems of legality and control, 335. — V. Summary, 338.